Functional Cereal Products in the Diet for Type 2 Diabetes Patients. (21st October 2019) - Krawęcka, Ada; Sobota, Aldona; Sykut-Domańska, Emilia
Abstract : Type 2 diabetes has become one of the major health problems of the modern world. It is assumed that environmental factors have a significant impact on the development of the disease, and great importance is ascribed to the diet, which can be modified accordingly. The diet can exert prophylactic and therapeutic effects; changes in the diet in advanced disease can improve the quality of life of diabetic patients and minimise the risk of complications, which are the direct cause of diabetes-related death. Functional food, which has a potentially health-enhancing effect in addition to its nutritional value, has been increasingly recognised and required. Cereal products are crucial in diabetic nutrition. Their function can additionally be enhanced by fortification with compounds with proven hypoglycaemic effects. Pasta has a low glycaemic index and is a good carrier of fortifying substances; hence, it can be highly recommended in diets for diabetic patients.